2020
DOI: 10.24856/mem.v35i1.1246
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Literacy Level and Demographic Factors on Investment Decision

Abstract: <p>The aim of this research is to find out the effect of financial literacy level and demographic factors on investment decision on government employees in Kalibawang Community Health Center, Kulon Progo, Yogyakarta. The population of this research is the government employees in Kalibawang Community Health Center, 29 of them are treated as the sample of this research. The sampling technique used in this research is purposive sampling. The respondents are those who  have  been  doing  investment. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 11 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…This result contradicts the research Violeta and Linawati (2019) and Ariadi et al (2015)which shows that gender influences a person's investment decisions. However, several studies agree with the results of this study, such as Wahyuni and Pramono (2021) and Senda et al (2020), that there is no influence between gender and one's investment decisions. In this study, this could be due to the similarity of the age range and level of education taken by both male and female respondents, so that the information obtained tends to be the same.…”
Section: Hypothesis Interpretationsupporting
confidence: 89%
“…This result contradicts the research Violeta and Linawati (2019) and Ariadi et al (2015)which shows that gender influences a person's investment decisions. However, several studies agree with the results of this study, such as Wahyuni and Pramono (2021) and Senda et al (2020), that there is no influence between gender and one's investment decisions. In this study, this could be due to the similarity of the age range and level of education taken by both male and female respondents, so that the information obtained tends to be the same.…”
Section: Hypothesis Interpretationsupporting
confidence: 89%
“…Researches conducted by Alaaraj and Bakri, (2020), Kumari, (2020), Abdeldayem, (2016), Awais et al, (2016), and Putri and Hamidi, (2019) showed impacts of financial literacy on investment decisions. However, there is also a research, conducted by Senda et al, (2020), finding that financial literacy did not influence investment decision. With such gap, researchers aim to examine the influence of financial literacy on investment decision.…”
Section: Research Frameworkmentioning
confidence: 96%
“…Previous researches in Indonesia focused solely on measurement of individual financial literacy index across professions including lecturers (Setyawati & Suroso, 2016), employees (Sobaya et al, 2016), and SME proprietors (Ariwibawa, 2016); (Hakim et al, 2017). Meanwhile, Arianti (2018) and Senda et al (2020) found that financial literacy had no significant influence on investment decision. Baihaqqy et al, (2020) in their research also state that high financial literacy will not have a major impact on investment decision making.…”
Section: Introductionmentioning
confidence: 99%
“…The research conducted by Agarwal et al, ( 2009) (as cited in Safira, 2018) shows that 30-40 year of age range has higher level of financial literacy. Suhartono and Qudsi (2009) (as cited in Senda et al, 2020) state that the age groups that can distinguish the investment decision period are as follows: 1) Group one, the group of people who have just started working, need fund for weeding preparation, and/or to get their first home (20-30 years old); 2) Group two, the group of people who are already married and have children (30-45 years old); 3) Group three, the group of people who need fund for their children"s tuition, marriage, treatment and pension preparation (45-55 years old); 4) Group four, the group of people who use their income for health and pension period (55 years old above). Academic Background.…”
Section: Demographic Aspectsmentioning
confidence: 99%